Development of smartphone contents to improve concentration based on EEG - Yun Seo, Ji; Hong Noh, Yun; Un Jeong, Do (International Journal of Engineering and Technology, 2018)
Background/Objectives: In recent years, the importance of concentration has been attracting attention in modern society, and interest in concentration-related diseases is increasing. As ADHD, one of the many diseases associated with concentration, has a great impact on academic and work efficiency and everyday life, so much research is underway on ADHD treatment.Methods/Statistical analysis: In this research, we implemented smartphone - based concentration training system which is easy to use in everyday life.NeuroNicle E2 of Laxtha Company was used for EEG measurement and EEG was measured by attaching to FP1 and FP2 of the frontal part according to the international 10-12 electrode arrangement method.EEG data received from the measuring section were extracted as frequency - specific EEG data using FFT and the concentration index was calculated by applying the CI algorithm.Findings: The system implemented in this study can control the aim point with the concentration of the user and perform the concentration training by feedback the changed EEG information to the user according to the movement of the aim point. Also, as the concentration of the user increases, the aim point moves to the center and the score of the game increases.Experiments were conducted using implemented EEG system and commercialization EEG system. EEGs were measured by EEG for 5 minutes each before, during, after training by wearing a wireless measuring instrument. The SMR wave, Mid_Î² wave, and Î¸ wave which are highly correlated with the concentration are indicated before, during, and after experiment, and it can be confirmed that each waveform has a significant change according to the experiment state. Also, it was confirmed that the concentration was the highest when training using this system and the concentration level was maintained even after the training.Improvements/Applications: The effectiveness of the system implemented in this research is verified and it can be expected that the user can utilize the portable device instead of the designated place such as the hospital or the professional institution to provide good training results through convenient and continuous concentration training.Â Â